Implementation of Risk Management in PT Len Industri - Case Study in LRT Bandung Raya (The Indonesian Journal of Business Administration, 2020)
Currently Indonesia is included in the category of developing countries. As a developing country, Indonesia under Joko Widodo's administration is very concerned with the infrastructure system.Based on 2019 APBN information, the infrastructure budget is directed at supporting the strengthening of connectivity, housing provision, and food security. A total of 415 Trillion Rupiah was budgeted in the 2019 APBN for infrastructure development. One infrastructure project that uses funds from the state budget is the LRT project in Indonesia.PT Len Industri is one of the Engineering Procurement Construction (EPC) companies in Indonesia that also plays a role in the continuity of the LRT project in Indonesia by offering railroad signaling development services. PT Len Industri through the Transportation Systems Business Unit has played a role in the development of the South Sumatra LRT signalling, Soekarno Hatta Airport Skytrain, Jakarta LRT, and Jabodebek LRT.But in the previous project, the Transportation Systems Business Unit faced several risks caused by project delays, such as Vandalism, Cost of Delay, Cost of Money, and Opportunity Costs. To minimize the risk of project delays in the future, this study aims to identify potential risks that may occur in new projects in the Transportation Systems Business Unit. LRT Bandung Raya became one of the projects in the planning stage at Unis Transportation Systems Business. This project became PT Len Industri's first project as an initiator. As an initiator of course the risks to be faced become more challenging. For this reason, this research will identify project risks using the risk criteria listed in PMBOK, use the McKinsey 7's framework and PESTEL methods to analyze the company's internal and external risks, and conduct risk assessments using the Analytical Hierarchy Process (AHP) to obtain priority risks in the project. The risk analysis in this study shows that LRT Bandung Raya has 4 extreme risks, 17 high risks, 18 moderate risks, and 2 low risks.Keywords: Risk assessment, risk identification, risk analysis, Analytical Hierarchy Process (AHP), Potential Risk